A retrospective study on intracranial mixed infection with tuberculous meningitis in Shenzhen, China - Mutong Fang; Sinian Li; Zhi Mao; Xuhui Liu; Xiaomin Wang; Shuihua Lu (Microbiology Spectrum, 2024)
ABSTRACT Tuberculous meningitis (TBM) is a prevalent global intracranial infection and the most lethal and disabling form of tuberculosis. TBM with mixed intracranial infections is clinically rare but has a higher mortality rate. To investigate the clinical characteristics of TBM with mixed intracranial infections, demographic and clinical data of TBM and pulmonary tuberculosis (PTB) patients admitted to Shenzhen Third People’s Hospital between January 2015 and October 2022 were collected anonymously. A total of 207 cases of TBM were diagnosed, of which 16 cases (7.73%) were TBM with mixed intracranial infections. The overall mortality rate of TBM cases was 16.4%, while the mortality rate of TBM cases with mixed intracranial infections was as high as 35.7%. Compared to simple TBM cases, TBM cases with mixed intracranial infections had severer clinical symptoms. The percentage of human immune deficiency virus (HIV)-positive TBM cases with mixed intracranial infections reached up to 68.8%. HIV co-infection, CD4+/CD8+ T-cell counts less than 1, cranial nerve impairment, paralysis, cerebral infarction, PRO less than 450 mg/L, WBC less than 10 × 106 /L, and CL more than 120 mmol/L were risk factors for TBM cases with mixed intracranial infections. Compared to PTB, HIV co-infection, CD4+ T cell less than 550 /uL, and age less than 45 years were risk factors for TBM, and TBM was associated with higher mortality rates. Our study provides additional data to better understand single TBM and TBM with mixed intracranial infections. More than two-thirds of TBM cases with mixed intracranial infections were HIV-positive. Clinicians should consider the possibility of multiple infections in people with TBM/HIV co-infection.IMPORTANCETBM can cause severe neurological damage and death, and TBM with mixed intracranial infections can exacerbate the damage and poor prognosis of the disease. TBM with mixed intracranial infections is a rare disease, which has led to an incomplete understanding of its clinical features. This study investigated the clinical features of TBM and its associated factors by comparing the characteristics of TBM with mixed intracranial infections, single TBM and pulmonary tuberculosis. This information will help to improve the understanding of TBM, diagnostic accuracy and treatment outcomes.